2023
DOI: 10.1021/acs.macromol.3c00462
|View full text |Cite
|
Sign up to set email alerts
|

Structural Effect of Organic Catalytic Pairs Based on Chiral Amino(thio)ureas and Phosphazene Bases for the Isoselective Ring-Opening Polymerization of Racemic Lactide

Abstract: Polymer materials featuring stereocontrolled monomer units often exhibit drastically different properties than their stereorandom counterparts. Control over the polymer tacticity thus represents a powerful means to access functional polymers of modular thermomechanical properties. In the present work, a series of chiral amino(thio)ureas (U1, TU1–TU5) are used in duos with phosphazene organic bases for the stereoselective ring-opening polymerization (ROP) of racemic lactide (rac-LA). These chiral binary organoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Here, we surveyed a series of CPI bases ( 1 – 7 ) in combination with U-1 for the room temperature polymerization of rac -LA (Table ). Each of the catalyst systems exhibited modest stereoselectivity, yielding PLAs with isotacticities ranging from Pm = 0.74–0.79, as determined by homonuclear decoupled 1 H NMR measurements. , While higher stereoselectivities have been observed with other (thio)­urea/base pairs, ,, the high activities for these urea/CPI catalysts (Tables and ) illustrate the range of reactivities and stereoselectivities that can be obtained by appropriate cocatalyst combinations.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Here, we surveyed a series of CPI bases ( 1 – 7 ) in combination with U-1 for the room temperature polymerization of rac -LA (Table ). Each of the catalyst systems exhibited modest stereoselectivity, yielding PLAs with isotacticities ranging from Pm = 0.74–0.79, as determined by homonuclear decoupled 1 H NMR measurements. , While higher stereoselectivities have been observed with other (thio)­urea/base pairs, ,, the high activities for these urea/CPI catalysts (Tables and ) illustrate the range of reactivities and stereoselectivities that can be obtained by appropriate cocatalyst combinations.…”
mentioning
confidence: 90%
“…Previously, bases such as 1,8-diazabicyclo[5.4.0]­undec-7-ene (DBU), , N -heterocyclic carbenes (NHCs), , or phosphazene derivatives have been used with success to provide highly active and/or (stereo)­selective OROPs when used in combination with (thio)­ureas. To expand the range of bases used with urea cocatalysts, we targeted cyclopropenimines (CPIs) as a class of accessible, soluble, stable, tunable, and inexpensive bases as cocatalysts with (thio)­ureas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Organocatalytic ring-opening polymerization (ROP) is a powerful method for generating polyesters and polycarbonates with exquisite control over the molecular weight and molecular weight distribution. Guanidine and (thio)­urea/base catalyst systems were among the first highly selective organocatalysts, demonstrating good control over molecular weight and dispersity. The development of anionic catalysts based on deprotonated (thio)­ureas marked a significant advance, as these catalysts retained the high selectivity of the (thio)­urea/base catalysts but were significantly more active. Moreover, their activities can be tuned by over 3 orders of magnitude by altering substituents on the (thio)­ureas. Due to the versatility of the anionic (thio)­urea catalysts, they have been widely adopted for the ROP of various monomers. Mechanistic and computational studies indicate that the activity of the anionic (thio)­urea catalysts derive from a bifunctional activation mechanism where the negatively charged nitrogen activates the propagating (or initiating) alcohol and the adjacent N–H hydrogen bond binds and positions the lactone to facilitate nucleophilic attack and formation of the tetrahedral intermediate (Figure a). …”
Section: Introductionmentioning
confidence: 99%
“…The use of organocatalysts, also known as metal-free catalysts, has considerably progressed in organic chemistry since 2000. In polymer chemistry, the ring-opening polymerization of lactide using 4-(dimethylamino)­pyridine as a catalyst was reported in 2002 as the first living polymerization using an organocatalyst . Organocatalytic polymerization has been widely expanded to use applicable cyclic monomers, such as cyclic esters, cyclic carbonates, and epoxides, and copolymerization of epoxide with CO 2 . These new precision polymerization systems require improvement in terms of polymerization activity, chemical selectivity, and polymer structure control. As a different type of polymerization, the group transfer polymerization (GTP) of polar monomers using 1-trimethylsiloxy-1-methoxy-2-methyl-1-propene (silyl ketene acetal, SKA Me ) enables the controlled/living system. Taton et al and Waymouth et al reported that N -heterocyclic carbene efficiently organocatalyzed the GTPs of methyl methacrylate and tert -butyl acrylate and the block GT copolymerization (GTcoP) of n -butyl acylate, N , N -dimethylaminoethyl acrylate, N , N -dimethylaminoethyl methacrylate, N , N -dimethylacrylamide (DMAm), and methacrylonitrile. We have reported that several types of organic molecules categorized as strong Bro̷nsted acids of trifluoromethanesulfonimide (Tf 2 NH) and pentafluorophenylbis­(triflyl)­methane (C 6 F 5 CHTf 2 ), strong Lewis acids of N -(trimethylsilyl)­bis­(trifluoromethanesulfonyl)­imide (Me 3 SiNTf 2 ) and tris­(pentafluorophenyl)­borane (B­(C 6 F 5 ) 3 ), and organic superbases of 1- tert -butyl-4,4,4-tris­(dimethylamino)-2,2-bis­[tris­(dimethylamino)­phosphoranylidenamino]-2Λ5,4Λ5-catenadi­(phosphazene) ( t -Bu-P 4 ) and 2,8,9-triisobutyl-2,5,8,9-tetraaza-1-phosphabicyclo[3.3.3]­undecane (T i BP) have effectively catalyzed the controlled/living GTP of (meth)­acrylate and acrylamide monomers. An optimal organocatalyst/initiator combination is crucial to achieving a controlled/living GTP.…”
Section: Introductionmentioning
confidence: 99%